The potential mechanism of Isodon suzhouensis against COVID-19 via EGFR/TLR4 pathways - Hong Duan; Wei Wang; Shu Li; Han Li; Ghulam Jilany Khan; Yong Ma; Fawang Liu; Kefeng Zhai; Henggui Hu; Zhaojun Wei (Food Science and Human Wellness)
Corona Virus Disease 2019 (COVID-19) has brought the new challenges to scientific research. Isodon suzhouensis has good anti-inflammatory and antioxidant stress effects, which is considered as a potential treatment for COVID-19. The possibility for the treatment of COVID-19 with I. suzhouensis and its potential mechanism of action were explored by employing molecular docking and network pharmacology. Network pharmacology and molecular docking were used to screen drug targets, and lipopolysaccharide (LPS) induced RAW264.7 and NR8383 cells inflammation model was used for experimental verification. Collectively a total of 209 possible linkages against 18 chemical components from I. suzhouensis and 1194 COVID-19 related targets were selected. Among these, 164 common targets were obtained from the intersection of I. suzhouensis and COVID-19. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enriched 582 function targets and 87 target proteins pathways, respectively. The results from molecular docking studies revealed that rutin, vitexin, isoquercitrin and quercetin had significant binding ability with 3 chymotrypsin like protease (3CLpro) and angiotensin converting enzyme 2 (ACE2). In vitro studies showed that I. suzhouensis extract (ISE) may inhibit the activation of PI3K/Akt pathway and the expression level of downstream proinflammatory factors by inhibiting the activation of epidermal growth factor receptor (EGFR) in RAW264.7 cells induced by LPS. In addition, ISE was able to inhibit the activation of TLR4/NF-κB signaling pathway in NR8383 cells exposed to LPS. Overall, the network pharmacology and in vitro studies conclude that active components from I. suzhouensis have strong therapeutic potential against COVID-19 through multi-target, multi-pathway dimensions and can be a promising candidate against COVID-19.